A two-step approach for sequencing spliceosome-related genes as a complementary diagnostic assay in MDS patients with ringed sideroblasts. (May 2017) - Janusz, Kamila; del Rey, Mónica; Abáigar, María; Collado, Rosa; Ivars, David; Hernández-Sánchez, María; Valiente, Alberto; Robledo, Cristina; Benito, Rocío; Díez-Campelo, María; Ramos, Fernando; Kohlmann, Alexander; et al.
Highlights: Mutations in spliceosome-related genes in 94.3% of MDS-RS. Presence of double mutations in the splicing machinery genes. Good prognosis of SF3B1 mutations in MDS-RS. Abstract: Our study aimed to analyze the presence of mutations in SF3B1 and other spliceosome-related genes in myelodysplastic syndromes with ringed sideroblasts (MDS-RS) by combining conventional Sanger and next-generation sequencing (NGS) methods, and to determine the feasibility of this approach in a clinical setting. 122 bone marrow samples from MDS-RS patients were studied. Initially, exons 14 and 15 of the SF3B1 gene were analyzed by Sanger sequencing. Secondly, they were studied by NGS covering besides SF3B1, SRSF2, U2AF1 and ZRSR2 genes. An 86% of all patients showed mutations in the SF3B1 gene. Six of them, which were not identifiable by conventional sequencing in the first diagnostic step, were revealed by NGS. In addition, 19.5% of cases showed mutations in other splicing genes: SRSF2, U2AF1, and ZRSR2 . Furthermore, 8.7% of patients had two mutations in SF3B1, SF3B1 and SRSF2, and SF3B1 and U2AF1, while 5.7% showed no mutations in the four spliceosome-related genes analyzed. The combined use of conventional Sanger and NGS allows the identification of mutations in spliceosome-related genes in almost all MDS patients with RS. This two-step approach is affordable and could be useful as a complementary technique in cases with an unclear diagnosis.